Geothermal Energy Systems 2010
DOI: 10.1002/9783527630479.ch6
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Use of EGS Reservoirs

Abstract: The principle for the energetic use of EGS (enhanced geothermal system) reservoirs is based on the production of a fluid which, carries the geothermal heat, in a production well, the extraction of heat from the fluid on the surface with a heat exchanger, and the reinjection of the cooled fluid into the reservoir in an injection well. The extracted heat can be used for heat, power, or chill provision (Figure 6.1). The different technical aspects and constraints which are related to such plants are the subject o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Further general information on fluid components and their effect in geothermal plants is addressed by Saadat et al [5].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Further general information on fluid components and their effect in geothermal plants is addressed by Saadat et al [5].…”
Section: +mentioning
confidence: 99%
“…In the binary unit, a working fluid with low boiling point is circulated, mostly because the direct use of the geothermal fluid in the conversion cycle is not as efficient from a thermodynamic point of view, e.g. [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to efficiently use a wider temperature domain, different applications demanding successively lower temperatures are ideally implemented in a cascade (International Energy Agency 2011;Líndal 1973). Space cooling is also possible using geothermal heat with a minimum temperature of 60°C to 70°C as an energy source for heat-driven sorption chillers instead of electrically driven compression chillers (International Energy Agency 2011;Líndal 1973;Saadat et al 2010). Another important field of application related to geothermal energy is the seasonal storage of solar energy or spare heat in deep aquifers (e.g., Stober and Bucher 2012).…”
Section: Background On Different Types Of Geothermal Utilizationsmentioning
confidence: 99%
“…Shallow geothermal energy refers to systems frequently using heat pumps for exploitation of near-surface environments characterized by temperatures <20°C and depths <400 m (Stober et al 2009). Deep geothermal energy refers to direct use of geothermal heat at temperatures >20°C (Líndal 1973;Saadat et al 2010). Major applications are in spas and swimming pools for balneological purposes; in industry, for process heating, in agriculture for greenhouse or soil heating or in aquaculture for pond heating.…”
Section: Background On Different Types Of Geothermal Utilizationsmentioning
confidence: 99%
“…However, for ORC cycles, unlike steam cycles, where the cycle designer has a great deal of choice in the shape of the T-s diagram of the fluid selected the reheat cycle loses its attractiveness and benefit. Indeed, the reheat cycle is not generally mentioned in geothermal texts (DiPippo, 2012;Saadat et al, 2010;Watson, 2013) and it was found that the cycle efficiency was similar to the basic Rankine cycle (Mago et al, 2007).…”
Section: Reheat Orcmentioning
confidence: 99%